Relationship of Overuse Injuries and Extrascholastic Sport Participation in High School Athletes 2009‐2010 through 2015‐2016. Issue 9 (22nd January 2020) - Ryder, Stephanie Cowherd; Gnirke, Matthew; Laker, Scott R.; Hoffmire, Claire; Comstock, R. Dawn
Abstract : Introduction: Overuse injuries (injuries due to repetitive loads with inadequate rest) can negatively affect high school athletes, but limited data exist on the effect of sports participation outside of the school‐sanctioned season on the development of overuse injuries. Objective: Compare overuse injury patterns among high school athletes who participate in extrascholastic athletics to those participating only in scholastic sports. Design: Descriptive cross‐sectional, secondary analysis of injury data collected on high school athletes across 22 sports over the 2009‐2010 through 2015‐2016 academic years. Setting: Deidentified data collected as part of the High School Reporting Information Online study (HS RIO). Participants: High school athletes from a large convenience sample of U.S. high schools. Main Outcome Measurements: Injury proportion ratios (IPRs) were computed overall and for individual sports to compare the proportion of overuse injuries in athletes competing in extrascholastic sports to athletes participating only in scholastic athletics. Results: Overall, extrascholastic athletes experienced a higher proportion of overuse injuries compared to scholastic‐only athletes (IPR = 1.21, 95% confidence interval [CI] 1.13‐1.30), but this association varied by sport. Among extrascholastic athletes, a higher proportion of overuse injuries occurred in those simultaneously playing the same sport outside the school setting (IPR = 1.32, 95% CI 1.11‐1.57) as well as having experienced an injury within the past year (IPR = 1.63, 95% CI 1.36‐1.95) compared to those sustaining non‐overuse injuries. Conclusions: Overuse injuries were associated with extrascholastic athletics and occurred in higher proportion in extrascholastic athletes who were playing the same sport in more than one league.